The Effect of Active Phase of the Work Material on Machining Performance of a NiTi Shape Memory Alloy - KAYNAK, YUSUF (SPRINGER, 2015)
Poor machinability with conventional machining processes is a major shortcoming that limits the manufacture of NiTi components. To better understand the effects of phase state on the machining performance of NiTi alloys, cutting temperature, tool-wear behavior, cutting force components, tool-chip contact length, chip thickness, and machined surface quality data were generated from a NiTi alloy using precooled cryogenic, dry, minimum quantity lubrication (MQL), and preheated machining conditions. Findings reveal that machining NiTi in the martensite phase, which was achieved through precooled cryogenic machining, profoundly improved the machining performance by reducing cutting force components, notch wear, and surface roughness. Machining in the austenite state, achieved through preheating, did not provide any benefit over dry and MQL machining, and these processes were, in general, inferior to cryogenic machining in terms of machining performance, particularly at higher cutting speeds.
Keywords: TOOL-WEAR; TI-6AL-4V; TRANSFORMATION; EVOLUTION; TITANIUM